Youth injury prevention in Canada: use of the Delphi method to develop recommendations. (December 2015) - Pike, Ian; Piedt, Shannon; Davison, Colleen; Russell, Kelly; Macpherson, Alison; Pickett, William
Abstract Background The Health Behaviour in School-aged Children Survey is one of very few cross-national health surveys that includes information on injury occurrence and prevention within adolescent populations. A collaboration to develop a Canadian youth injury report using these data resulted in, Injury among Young Canadians: A national study of contextual determinants . The objective of this study was to develop specific evidence-based, policy-oriented recommendations arising from the national report, using a modified-Delphi process with a panel of expert stakeholders. Method Eight injury prevention experts and a 3-person youth advisory team associated with a Canadian injury prevention organization (Parachute Canada) reviewed, edited and commented on report recommendations through a three-stage iterative modified-Delphi process. Results From an initial list of 27 draft recommendations, the modified-Delphi process resulted in a final list of 19 specific recommendations, worded to resonate with the group(s) responsible to lead or take the recommended action. Two recommendations were rated as "extremely important" or "very important" by 100 % of the expert panel, two were deleted, a further two recommendations were deleted but the content included as text in the report, and four were merged with other existing recommendations. Conclusions The modified-Delphi process was an appropriate method to achieve agreement on 19 specific evidence-based, policy-oriented recommendations to complement the national youth injury report. In providing their input, it is noted that the injury stakeholders each acted as individual experts, unattached to any organizational position or policy. These recommendations will require multidisciplinary collaborations in order to support the proposed policy development, additional research, programming and clear decision-making for youth injury prevention.